The Impact And Response Of Maritime Southeast Asian Countries to Economic Dynamics During The Covid-19 Pandemic - A Darmayadi; M.A Aditiya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to analyze the responses made by each Maritime Southeast Asian country in dealing with economic dynamics during the Covid-19 pandemic. The Southeast Asia region, especially Maritime Southeast Asia, has experienced relatively rapid growth in the last few decades, so several countries in this region are classified as newly industrialized countries such as Indonesia, Malaysia and the Philippines. However, this economic development has been disrupted due to the Covid-19 pandemic since the beginning of 2020. This pandemic has left a sizeable impact on sectors in the world, including in Maritime Southeast Asian countries. The method used in writing this paper is using a qualitative method, this journal will describe the impact of using the data obtained through the Literature Study method. In its development, the Covid-19 pandemic has had a considerable impact on the economies of countries in the Maritime Southeast Asia region. Countries in the region recorded a slowdown in economic growth, most of them even experienced a recession. The result of this research are All countries in the Maritime Southeast Asia region experienced negative economic growth during 2020 except for Brunei. The governments of each country have their policies in dealing with existing problems, starting from providing financial assistance in the form of an economic stimulus package as well as issuing other fiscal and monetary policies